Effect of nozzle box arrangement on the aerodynamic performance of a single stage partial admission turbine. (August 2019) - Pan, Yang; Yuan, Qi; Niu, Guangshuo; Gu, Jiawei; Zhu, Guangyu
Highlights: The effects of nozzle box arrangement on partial admission turbine are revealed. Partial admission losses as well as mixing losses introduced by partial admission are analyzed. The blade load changes at the transition region between inlet section and blockage are presented. Small circumferential gap can avoid negative blade tangential force downstream the gap region. Abstract: For partial admission turbine, nozzle box arrangement has a profound impact on its aerodynamic performance. Hence, a single stage partial admission turbine with two nozzle boxes under eight arrangements was numerically investigated using CFD of three-dimensional Reynolds-averaged Navier-Stokes and SST turbulence model. Additionally, the turbine at full admission was also studied for comparison. The results show that the extra losses including sector end loss, pumping loss and mixing loss caused by partial admission decelerate to increase with circumferential gaps between nozzle boxes. The detailed loss distributions with a different circumferential gap are illustrated. Moreover, the non-uniformity in static pressure, Mach number distributions and streamlines downstream the gap region are influenced obviously by circumferential gap. Multiple low Mach number lines formed by mixing effect between active fluid and stagnant fluid are also captured. Further, the analysis of excitation force shows that the circumferential gap also changes the blade tangential force and rotor radial force distributions significantly while the change of blade axial force and rotor axial force is relatively lower.